Honeycomb catalyst and preparation method thereof
By regulating the water content of calcium silicate embryos in CO2 atmosphere and curing the catalyst, the problem of high catalyst shedding rate in honeycomb catalysts is solved, and the stability and efficiency of the catalyst are improved.
Patent Information
- Application Number
- CN202411938462.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-29
AI Technical Summary
The catalyst shedding rate in honeycomb catalysts is relatively high and is susceptible to factors such as mechanical impact and chemical corrosion, resulting in a decrease in the effectiveness of the catalyst.
By regulating the water content in the calcium silicate embryo containing the catalyst in the atmosphere of CO2, CO2 is dissolved into the embryo, and the calcium silicate is cured, thereby reducing the catalyst shedding rate.
It effectively reduces the shedding rate of the catalyst, improves the compressive strength and other properties of the honeycomb catalyst, and enhances its stability and efficiency in photocatalytic degradation.
Smart Images

Figure CN119897084A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalyst carriers, and in particular to a honeycomb catalyst and a preparation method thereof. Background Art
[0002] Honeycomb ceramic monolithic catalysts are generally used to catalyze the degradation of organic wastewater in the field of photocatalysis. Under normal conditions, one or more active catalysts are loaded, such as transition metal oxides such as TiO2, ZnO, and MnO2. Under ultraviolet light irradiation, they absorb photon energy, generate excited electrons and holes, and react with oxygen molecules or water molecules to produce active free radicals to degrade organic pollutants in water.
[0003] The catalyst loading in honeycomb ceramics is usually done by using the finished product after sintering the honeycomb ceramics. Generally, the precursor is deposited in the pores of the honeycomb ceramics by impregnation, precipitation, sol-gel and other methods, and then calcined at 400℃ to 600℃ to generate the catalyst loaded on the surface of the honeycomb ceramics. However, the high porosity and specific surface area of honeycomb ceramics also make them more susceptible to mechanical impact and chemical corrosion, which can easily lead to the problem of catalyst shedding.
[0004] Chinese patent application 201610978890.2 discloses a honeycomb ceramic integral photocatalyst and its preparation method and application, wherein TiO2 is fixed to a cordierite honeycomb ceramic with an active alumina coating by a dip coating method. In this method, the catalyst shedding rate is less than 1%. However, it can be seen from the specification that the catalyst is on the surface of the honeycomb ceramic and is still susceptible to factors such as mechanical impact and chemical corrosion, resulting in catalyst shedding.
[0005] Chinese patent application 201010290153.6 discloses a process for preparing a sinter-free Y2O3-TiO2 catalyst honeycomb body. By using magnesium oxychloride gelation, i.e. MgO-MgCl2-H2O as a curing agent, the body is cured at room temperature into a catalyst honeycomb body that can meet the needs of flue gas desulfurization and denitrification. However, the curing time required for this method is 3 days, which is relatively long.
[0006] The present application has found through research that using calcium silicate powder as a catalyst carrier can also achieve a good loading effect.
[0007] The problem that this solution needs to solve is: how to reduce the catalyst shedding rate in the honeycomb catalyst. Summary of the invention
[0008] The purpose of the present invention is to provide a honeycomb catalyst and a preparation method thereof. In a CO2 atmosphere, the water content in a calcium silicate embryo containing the catalyst is regulated so that CO2 dissolves into the embryo to solidify the calcium silicate, thereby reducing the shedding rate of the catalyst.
[0009] To achieve the above-mentioned purpose, the present application discloses a honeycomb catalyst, which is prepared by solidifying a calcium silicate embryo containing the catalyst by CO2;
[0010] The mass of water in the calcium silicate embryo is 5-15% of the mass of the calcium silicate embryo;
[0011] In a specific implementation case of the present application, the mass of water in the calcium silicate embryo can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% of the mass of the calcium silicate embryo;
[0012] The participation of water is crucial in the carbonization process of calcium silicate minerals. The main stages include the dissolution of cations in the minerals, the dissolution of CO2 in water and its ionization into carbonate ions, and the combination of cations and carbonate ions in the aqueous solution. For the formed embryo, a large amount of water fills the gaps between particles, blocking the channel for CO2 gas to migrate into the interior of the material, making it difficult for the internal carbonization reaction to proceed. Therefore, it is necessary to control the moisture content in the embryo to the most favorable condition for the carbonization reaction.
[0013] Preferably, the calcium silicate embryo contains a catalyst and calcium silicate powder;
[0014] The catalyst is selected from at least one of TiO2, ZnO and MnO2;
[0015] The calcium silicate powder is selected from at least one of γ-type dicalcium silicate powder, tricalcium disilicate powder and monocalcium silicate powder;
[0016] The mass of the catalyst is 2-5% of the mass of the calcium silicate powder;
[0017] Further preferably, in the specific implementation cases of the present application, the mass of the catalyst can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, or 5.0% of the mass of the calcium silicate powder.
[0018] Preferably, the calcium silicate embryo also contains a binder and a plasticizer;
[0019] The binder is selected from at least one of hydroxypropyl methylcellulose, povidone, and carboxymethyl cellulose;
[0020] The plasticizer is selected from at least one of glycerol, dibutyl phthalate, and dioctyl adipate;
[0021] The mass of the adhesive is 2-5% of the mass of the calcium silicate powder, and the mass of the plasticizer is 2-5% of the mass of the calcium silicate powder.
[0022] In the specific implementation cases of the present application, the mass of the adhesive may be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, or 5.0% of the mass of the calcium silicate powder;
[0023] The mass of the plasticizer can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, or 5.0% of the mass of the calcium silicate powder.
[0024] Further preferably, the binder is hydroxypropyl methylcellulose with a viscosity of 5000 to 100000 Pa·S;
[0025] The plasticizer is glycerol.
[0026] In addition, a method for preparing the honeycomb catalyst is also disclosed, comprising the following steps:
[0027] Step 1: weigh calcium silicate powder, water, a catalyst, a binder, and a plasticizer, mix them, knead the mud, repeat 2 to 4 times, press and shape, and dry to obtain a calcium silicate embryo;
[0028] Step 2: Curing the calcium silicate embryo to obtain a honeycomb catalyst.
[0029] Preferably, the mass of water is 20-30% of the mass of the calcium silicate powder;
[0030] In the specific implementation cases of the present application, the mass of water can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30% of the mass of the calcium silicate powder.
[0031] Preferably, the pressure of the press molding is 10 to 20 MPa.
[0032] Preferably, in step 1, the drying temperature is 30-60° C. and the drying time is 4-8 hours.
[0033] Preferably, the specific operation of curing in step 2 is: placing the calcium silicate embryo in an atmosphere with a temperature of 5 to 90° C., a relative humidity of 30 to 80%, an air pressure of 0.1 to 0.4 MPa, and a CO2 concentration of 60 to 99% for curing for 1 to 24 hours.
[0034] The beneficial effects of the present invention are:
[0035] The present invention provides a honeycomb catalyst and a preparation method thereof. In a CO2 atmosphere, the water content in a calcium silicate embryo is adjusted so that CO2 is fully dissolved and diffused into the embryo, reacting with the calcium silicate to solidify the various components of the material, thereby reducing the shedding rate of the catalyst. The calcium silicate embryo also contains a plasticizer and an adhesive, which can improve the compressive strength and other properties of the prepared honeycomb catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The figure is a diagram showing the degradation effect of the honeycomb catalyst prepared in Example 1 on the methyl orange solution at 20 min, 40 min, 60 min and 80 min. DETAILED DESCRIPTION
[0037] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0038] Example 1
[0039] Step 1: Weigh 5kg of γ-type dicalcium silicate powder, mix it with water, TiO2, hydroxypropyl methylcellulose with a viscosity of 50000Pa·S, and glycerin, knead the mud under a vacuum environment of -0.07Mpa and repeat the kneading for 3 times. After the kneading is completed, the kneaded mud material is kept under a pressure of 5MPa for 7 minutes, and then continuously extruded at a pressure of 15MPa, and dried at 40°C for 6h to obtain a calcium silicate embryo in which the mass of water is 10% of the mass of the embryo;
[0040] The mass of water, TiO2, hydroxypropyl methylcellulose and glycerol are 25%, 3.5%, 3.5% and 3.5% of the mass of γ-type dicalcium silicate powder respectively;
[0041] Step 2: Curing the calcium silicate embryo for 12 hours in an atmosphere of a temperature of 55° C., a relative humidity of 55%, an air pressure of 0.25 MPa and a CO2 concentration of 80% to obtain a honeycomb catalyst.
[0042] Example 2
[0043] Step 1: Weigh 5kg of γ-type dicalcium silicate powder, mix it with water, TiO2, hydroxypropyl methylcellulose with a viscosity of 5000Pa·S, and glycerin, knead the mud under a vacuum environment of -0.1Mpa and repeat the kneading twice, after the mud kneading is completed, keep the pressure of the kneaded mud material at a pressure of 5MPa for 5min, then continuously extrude it at a pressure of 10MPa, and dry it at 30°C for 8h to obtain a calcium silicate embryo in which the mass of water is 10% of the mass of the embryo;
[0044] The mass of water, TiO2, hydroxypropyl methylcellulose and glycerol are 30%, 2%, 5% and 2% of the mass of γ-type dicalcium silicate powder respectively;
[0045] Step 2: Curing the calcium silicate embryo for 24 hours in an atmosphere of a temperature of 5° C., a relative humidity of 80%, an air pressure of 0.1 MPa and a CO2 concentration of 80% to obtain a honeycomb catalyst.
[0046] Example 3
[0047] Step 1: Weigh 5kg of γ-type dicalcium silicate powder, mix it with water, TiO2, hydroxypropyl methylcellulose with a viscosity of 100000Pa·S, and glycerin, knead the mud under a vacuum environment of -0.05Mpa and repeat the kneading 4 times, after the mud kneading is completed, keep the pressure of the kneaded mud material at a pressure of 5MPa for 10min, then continuously extrude it at a pressure of 20MPa, and dry it at 60℃ for 4h to obtain a calcium silicate embryo in which the mass of water is 10% of the mass of the embryo;
[0048] The mass of water, TiO2, hydroxypropyl methylcellulose and glycerol are 20%, 5%, 2% and 5% of the mass of γ-type dicalcium silicate powder respectively;
[0049] Step 2: Curing the calcium silicate embryo for 1 hour in an atmosphere of a temperature of 90° C., a relative humidity of 30%, an air pressure of 0.4 MPa and a CO2 concentration of 80% to obtain a honeycomb catalyst.
[0050] Example 4
[0051] The method is basically the same as Example 1, except that the mass of water in the calcium silicate embryo is 5% of the mass of the calcium silicate embryo.
[0052] Example 5
[0053] The method is substantially the same as Example 1, except that the mass of water in the calcium silicate embryo is 15% of the mass of the calcium silicate embryo.
[0054] Example 6
[0055] It is basically the same as Example 1, except that the CO2 concentration in the curing atmosphere is 60%.
[0056] Example 7
[0057] It is basically the same as Example 1, except that the CO2 concentration in the curing atmosphere is 99%.
[0058] Example 8
[0059] The method is basically the same as Example 1, except that the CO2 concentration in the curing atmosphere is 30%.
[0060] Example 9
[0061] It is basically the same as Example 1, except that the curing process is carried out directly in the air.
[0062] Example 10
[0063] It is basically the same as Example 1, except that the calcium silicate powder is tricalcium disilicate powder.
[0064] Comparative Example 1
[0065] The method is basically the same as Example 1, except that the mass of water in the calcium silicate embryo is 3% of the mass of the calcium silicate embryo.
[0066] Comparative Example 2
[0067] The method is basically the same as Example 1, except that the mass of water in the calcium silicate embryo is 20% of the mass of the calcium silicate embryo.
[0068] Performance Testing:
[0069] 1. Catalyst shedding rate: 100g of the honeycomb catalyst prepared in Examples 1-10 or Comparative Examples 1-2 was taken and the catalyst desorption rate was measured using an SB-120D ultrasonic cleaning machine produced by Ningbo Xinzhi Biotechnology Co., Ltd. The honeycomb catalyst samples before and after ultrasonic treatment were placed in an oven at 105°C for 3 hours and the dried samples were weighed. The desorption rate (Δm) can be calculated from the dry mass of the sample before and after ultrasonic treatment using Formula I:
[0070] Formula I:
[0071] Wherein: Δm is the catalyst desorption rate, %; m0 is the dry mass of the honeycomb catalyst before ultrasound, that is, m0 = 100g; m is the dry mass of the honeycomb ceramic after ultrasound, g.
[0072] The performance test results are shown in Table 1:
[0073] Table 1
[0074] Group Catalyst shedding rate % Group Catalyst shedding rate % Example 1 0.03 Example 7 0.02 Example 2 0.08 Example 8 1.53 Example 3 0.12 Example 9 ×(Cannot be measured) Example 4 0.33 Example 10 0.06 Example 5 0.42 Comparative Example 1 13.20 Example 6 0.20 Comparative Example 2 9.64
[0075] Conclusion analysis:
[0076] 1. It can be seen from Examples 1-3 that when the composition of the honeycomb catalyst and the process parameters of the maintenance are changed, the catalyst shedding rate in the obtained honeycomb catalyst will also increase. Therefore, it can be seen that the process conditions in Example 1 are the optimal conditions.
[0077] 2. It can be seen from Examples 1 and 4-5 that when the water content in the calcium silicate embryo is changed under the condition that the CO2 atmosphere concentration remains unchanged, since CO2 needs to react with water to generate carbonic acid and solidify with calcium silicate, when the mass of water in the embryo decreases, the amount of carbonic acid generated will be insufficient for complete solidification and affect the catalyst shedding rate; when the mass of water in the embryo increases, excess water fills the gaps between the particles, hindering the channel for CO2 gas to migrate into the interior of the material, making the internal carbonization reaction difficult, and also affecting the catalyst shedding rate.
[0078] 3. It can be seen from Examples 1 and 6-7 that, when the water content of the calcium silicate embryo body remains unchanged, as the concentration of CO2 in the atmosphere increases, the curing effect of the catalyst in the embryo body becomes better and better. However, it can be seen from Examples 1 and 7 that when the concentration of CO2 in the atmosphere increases to a certain level, the improvement in the curing effect of the catalyst in the embryo body is already small;
[0079] It can be seen from Example 1 and Example 8 that when the concentration of CO2 in the atmosphere is only 30%, the embryo body cannot be cured within a certain period of time, resulting in a high catalyst shedding rate of 1.53%.
[0080] Further observation of Example 9 shows that when the calcium silicate embryo was placed in an air atmosphere for curing, because the concentration of CO2 in the air was thinner, when the catalyst shedding rate test was performed, the embryo disintegrated and the measurement could not be completed.
[0081] 4. It can be seen from Example 1 and Example 10 that when the calcium silicate component in the calcium silicate embryo is changed, different calcium silicate components have different curing effects on the catalyst, but good results can also be achieved.
[0082] 5. It can be seen from Example 1 and Comparative Examples 1-2 that when the water content in the calcium silicate embryo is further reduced or increased, CO2 cannot generate enough carbonic acid or CO2 cannot enter the interior of the calcium silicate embryo due to excess water blocking, thereby reducing the curing effect of the catalyst and increasing the catalyst shedding rate.
[0083] Photocatalytic degradation efficiency:
[0084] Under ultraviolet light irradiation, the honeycomb catalyst reacts with methyl orange at a concentration of 5 mg·L -1 Photocatalytic degradation of methyl orange solution.
[0085] Test process: Add 5 mg·L -1 A methyl orange solution was prepared, and the honeycomb catalyst prepared in Example 1 was suspended with a thin iron wire and immersed in the solution. A 250W ultraviolet lamp was used to illuminate the material, and a homemade paper shell was used to cover the entire photocatalytic device to ensure that the light energy was absorbed and utilized as much as possible. A pure solvent (distilled water) was used for baseline correction to eliminate errors caused by solvent absorbance or background interference. The supernatant was taken every 20 minutes and centrifuged for 2 minutes using a centrifuge. After that, the solution to be tested was added to an optical absorption cuvette, and its absorbance was tested at 462.5nm using an ultraviolet-visible spectrophotometer (UV-Vis, UV-2500). Substituting into the absorbance-concentration relationship, the solution concentration was obtained, and then the photocatalytic degradation rate of the solution under the catalytic time was obtained. The degradation rate of methyl orange is obtained by formula II and formula III:
[0086] Formula II: C = (A + 0.0019) / 0.06719
[0087] Formula III:
[0088] Where: η is the degradation rate of methyl orange solution, %; C0 is the initial concentration of methyl orange solution, mg·L -1 ; C is the concentration of methyl orange solution measured at different times, mg·L -1 , A is the absorbance.
[0089] The degradation rate of the honeycomb catalyst prepared in Example 1 is shown in Table 2, and the catalytic effect is shown in Table 2. Figure 1 As shown:
[0090] Table 2
[0091]
[0092] It can be seen from Table 2 that the catalyst solidified into the interior of the calcium silicate embryo can also have a good catalytic degradation effect.
[0093] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A honeycomb catalyst, characterized in that: It is obtained by solidifying a calcium silicate embryo containing a catalyst by CO2; The mass of water in the calcium silicate embryo is 5-15% of the mass of the calcium silicate embryo.
2. The honeycomb catalyst according to claim 1, characterized in that: The calcium silicate embryo contains a catalyst and calcium silicate powder; The catalyst is selected from at least one of TiO2, ZnO, and MnO2; The calcium silicate powder is selected from at least one of γ-type dicalcium silicate powder, tricalcium disilicate powder, and monocalcium silicate powder; The mass of the catalyst is 2-5% of the mass of the calcium silicate powder.
3. The honeycomb catalyst according to claim 1, characterized in that: The calcium silicate embryo also contains a binder and a plasticizer; The binder is selected from at least one of hydroxypropyl methylcellulose, povidone, and carboxymethyl cellulose; The plasticizer is selected from at least one of glycerol, dibutyl phthalate, and dioctyl adipate; The mass of the adhesive is 2-5% of the mass of the calcium silicate powder, and the mass of the plasticizer is 2-5% of the mass of the calcium silicate powder.
4. A method for preparing a honeycomb catalyst as claimed in claims 1-3, characterized in that: The following steps are involved: Step 1: Weigh calcium silicate powder, water, catalyst, binder, and plasticizer, mix and knead the mixture 2 to 4 times, extrude and shape the mixture, and dry the mixture to obtain a calcium silicate embryo; Step 2: Curing the calcium silicate embryo to obtain a honeycomb catalyst.
5. The preparation method according to claim 4, characterized in that: The mass of the water is 20-30% of the mass of the calcium silicate powder.
6. The preparation method according to claim 4, characterized in that: The extrusion molding pressure is 10-20 MPa.
7. The preparation method according to claim 4, characterized in that: In step 1, the drying temperature is 30-60° C. and the drying time is 4-8 hours.
8. The preparation method according to claim 1, characterized in that: The specific operation of curing in step 2 is: placing the calcium silicate embryo in an atmosphere with a temperature of 5 to 90° C., a relative humidity of 30 to 80%, an air pressure of 0.1 to 0.4 MPa, and a CO2 concentration of 60 to 99% for curing for 1 to 24 hours.
Citation Information
Patent Citations
Process for preparing sintering-free Y2O3-TiO2 catalyst honeycomb
CN102000557A
Honeycomb ceramic monolithic photocatalyst as well as preparation method and application of honeycomb ceramic monolithic photocatalyst
CN106563430A